Analisis Penentuan Rute Distribusi Produk Makanan Menggunakan Pendekatan Algoritma Ant Colony Optimization (ACO) PT. Cipta Langgeng Mitra Sukses: Penelitian - Wayan Andika Riyantara; Rudolf Simatupang; Eduart Wolok; Idham Halid Lahay; Hendra Uloli (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the distribution route determination of PT. Cipta Langgeng Mitra Sukses's food products using the Ant Colony Optimization (ACO) method. This study uses a quantitative approach to design the optimal distribution route at PT. Cipta Langgeng Mitra Sukses in Gorontalo Regency. Through Ant Colony Optimization (ACO) algorithm simulation, this study analyzes the variables of distance, time, and cost with data obtained from literature studies, interviews, and field observations. The results of this study indicate that the optimal route formed is able to minimize travel distance, time, and operational costs. Fleet 1 traveled a distance of 38.7 km in 79 minutes and costs Rp26,316, while Fleet 2 traveled 37.2 km in 99 minutes and costs Rp25,296. The evaporation mechanism and pheromone intensity influence the route selection, where the 5th route for Fleet 1 and the 1321st route for Fleet 2 are the fastest and most efficient routes. These findings prove that Ant Colony Optimization (ACO) is effective in determining the optimal distribution route for the company.